Inhibitory Effects of Glycyrrhetinic Acid on DNA Polymerase and Inflammatory Activities. (14th July 2011) - Ishida, Tsukasa; Mizushina, Yoshiyuki; Yagi, Saori; Irino, Yasuhiro; Nishiumi, Shin; Miki, Ikuya; Kondo, Yasuyuki; Mizuno, Shigeto; Yoshida, Hiromi; Azuma, Takeshi; Yoshida, Masaru
Abstract : We investigated the inhibitory effect of three glycyrrhizin derivatives, such as Glycyrrhizin (compound 1 ), dipotassium glycyrrhizate (compound 2 ) and glycyrrhetinic acid (compound 3 ), on the activity of mammalian pols. Among these derivatives, compound 3 was the strongest inhibitor of mammalian pols α, β, κ, and λ, which belong to the B, A, Y, and X families of pols, respectively, whereas compounds 1 and 2 showed moderate inhibition. Among the these derivatives tested, compound 3 displayed strongest suppression of the production of tumor necrosis factor- α (TNF- α ) induced by lipopolysaccharide (LPS) in a cell-culture system using mouse macrophages RAW264.7 and peritoneal macrophages derived from mice. Moreover, compound 3 was found to inhibit the action of nuclear factor- κ B (NF- κ B) in engineered human embryonic kidney (HEK) 293 cells. In addition, compound 3 caused greater reduction of 12- O -tetradecanoylphorbol-13-acetate-(TPA-) induced acute inflammation in mouse ear than compounds 1 and 2 . In conclusion, this study has identified compound 3, which is the aglycone of compounds 1 and 2, as a promising anti-inflammatory candidate based on mammalian pol inhibition.